Capecitabine maintenance therapy in patients with recurrent or metastatic breast cancer - Si,W. (2013)
Our objective was to investigate the efficacy and safety of capecitabine maintenance therapy (CMT) after capecitabine-based combination chemotherapy in patients with metastatic breast cancer. The clinical data of 139 metastatic breast cancer patients treated from March 2008 to May 2012 with capecitabine-based combination chemotherapy were retrospectively analyzed. When initial disease control was achieved by the combination chemotherapy, we used CMT for 50 patients, while 37 patients were treated with a different (non-CMT) maintenance therapy. We compared time to progression (TTP), objective response rate, disease control rate, clinical benefit rate, and safety of the two groups, and a sub-group analysis was performed according to pathological characteristics. Sixty-four percent of the patients received a median of six cycles of a docetaxel+capecitabine combination chemotherapy regimen (range 1-45); the median TTP (MTTP) for the complete treatment was 9.43 months (95%CI=8.38-10.48 months) for the CMT group and 4.5 months (95%CI=4.22-4.78 months; P=0.004) for the non-CMT group. The MTTPs for the maintenance therapies administered after the initial capecitabine combined chemotherapy were 4.11 months (95%CI=3.34-4.87 months) for the CMT group and 2.0 months (95%CI=1.63-2.38 months) for the non-CMT group. Gastrointestinal side effects, decreased white blood cells and palmar-plantar erythrodysesthesia were the main adverse reactions experienced with the combination chemotherapies, CMT and non-CMT treatments. No significant differences in the incidence of adverse reactions were detected in the CMT and non-CMT patients. After initial disease control was achieved with the capecitabine-based combination chemotherapy, CMT can significantly prolong TTP rates with a favorable safety profile.